Artificial Intelligence Integrated Social Distancing Analyzer using Deep Neural Nets - Smith , Luren (International Journal of Interactive Mobile Technologies (iJIM), 2022)
Corona Virus Disease (COVID) has so far infected millions of individuals, claiming the lives of tens of thousands. Italy and the United States, two major international powers, are particularly hard hit, with millions of people dead per day. For nations like as India, France, Germany and Spain, Corona has wreaked havoc on the global economy. Throughout the globe, this devastation has been inflicted by this catastrophic virus. After the lockdown limitations have been relaxed, it is necessary to guarantee that social distance is practised at the locations since no treatment has been identified thus far. After the lockdown restrictions were relaxed in countries like India, where fewer instances were recorded, the nation saw an increase in cases. Implementation of social distancing systems is the topic of this study, which employs sophisticated libraries to keep track of the distance between people in real time and implement the system. Deploying deep learning and Raspberry Pi, we want to change the system of social distance by using a small number of sensors to acquire real-time data. Corona Virus Disease (COVID) has so far infected millions of individuals, claiming the lives of tens of thousands. Italy and the United States, two major international powers, are particularly hard hit, with millions of people dead per day. For nations like India, France, Germany, and Spain, Corona has wreaked havoc on the global economy. Throughout the globe, this devastation has been inflicted by this catastrophic virus. After the lockdown limitations have been relaxed, it is necessary to guarantee that social distance is practiced at the locations since no treatment has been identified thus far. After the lockdown restrictions were relaxed in countries like India, where fewer instances were recorded, the nation saw an increase in cases. Implementation of social distancing systems is the topic of this study, which employs sophisticated libraries to keep track of the distance between people in real-time and implement the system. Deploying deep learning and Raspberry Pi, we want to change the system of social distance by using a small number of sensors to acquire real-time data.